Digital work and play: Mobile technologies and new ways of feeling at home. (February 2018) - Pink, Sarah; Hjorth, Larissa; Horst, Heather; Nettheim, Josh; Bell, Genevieve
In this article, we advance current discussions by bringing together debates about digital play and digital labour. We consider everyday life entanglements of mobile media and digital work and play at home. To develop this argument, we analyse the embodied and affective dimensions of mundane everyday life at home with digital media through the concepts of atmosphere and ambient play. We argue that attention to how digital play is implicated in the constitution of texture and feeling of the everyday needs to underpin our understanding of how mobile media are participating in shifts in everyday experiences of work and home. In doing so, we draw on ethnographic research undertaken with middle-class families in Melbourne, Australia.